(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Derived from the health contingency, a series of problems have been generated that have directly affected companies, in that sense the effects on marketing are low sales, distribution channels, new forms of consumption, use of technologies, new needs among others; which are reflected in the positioning and competitiveness of companies. The work is about an exploratory study carried out to MSMEs in the service sector, a specific case of restaurants in the city of Chilpancingo, Guerrero, in order to know the marketing Social Responsibility actions that have been applied to face the COVID-19 pandemic and take care of the health of its consumers and employees. Among the findings found in the study regarding the health of consumers and restaurant employees are a reduction in the number of diners, space separation, placement of a sanitizing mat, antibacterial gel, temperature meter, taking orders online, social networks , telephone sales, card charges and bank deposit, protection kit for workers, communication of health information, etc.